Oak somatic and gametic embryos maturation is affected by charcoal and specific aminoacids mixture - Pintos, Beatriz; Manzanera, Jose a; Bueno, M. Angeles (Annals of Forest Science, 2010)
• Development of both somatic and gametic embryogenesis has many applications in clonal forestry and genetic improvement, for instance as mass-propagation of genetically improved plants and production of pure lines through doubled-haploid plant regeneration from gametic embryos. • The goal of this work was to improve growth, maturation and plantlet regeneration of cork oak (Quercus suber L.) embryos from both somatic and gametic origin. • Activated charcoal promoted a signiﬁcant increase in growth in terms of relative size and weight of both somatic and doubled-haploid embryos, as well as a more eﬃcient control of secondary somatic embryogenesis during development. A signiﬁcant interaction was also observed with amino acid nutrition. While some amino acids (i.e., glutamine, arginine or asparagine) did not show signiﬁcant diﬀerences with the controls, a mixture of these three amino acids or gamma amino butyric acid stimulated embryo growth. The highest survival rate during acclimation of plantlets from both somatic and doubled-haploid origin was obtained when the embryos had been previously cultured on basal medium with 3% sucrose and 1% activated charcoal for two months at 4 ◦ C and germinated on medium supplemented with 6-benzylaminopurine and indole-3-butyric acid. • We obtained more than 900 cork oak plantlets acclimated from several embryogenic lines, with a high survival rate, demonstrating that this methodology is applicable for large scale plantlet production. We also report the ﬁrst regeneration of doubled-haploid plantlets in cork oak.
Keywords: activated charcoal; amino acids; Cork oak; gametic embryo; plantlet acclimation

Microspore-derived embryos from Quercus suber anthers mimic zygotic embryos and maintain haploidy in long-term anther culture. - Bueno, María a; Gomez, Arancha; Sepulveda, Federico; Seguí, José M; Testillano, Pilar S; Manzanera, Jose a; Risueño, Maria-Carmen (Journal of plant physiology, 2003)
Microspore-derived embryos produced from cork oak anther cultures after long-term incubations (up to 10-12 months) were analysed in order to determine the genetic variability and ploidy level stability, as well as morphology, developmental pattern and cellular organisation. Most of the embryos from long-term anther cultures were haploid (90.7%), corresponding to their microspore origin. The presence of a low percentage of diploid embryos (7.4%) was observed. Microsatellite analysis of haploid embryos, indicated different microspores origins of the same anther. In the diploid embryos, homozygosity for different alleles was detected from anther wall tissues, excluding the possibility of clonal origin. The maintenance of a high proportion of haploid embryos, in long-term anther cultures, is similar in percentage to that reported in embryos originating after 20 days of plating (Bueno et al. 1997). This suggests that no significant alterations in the ploidy level occurred during long incubations (up to 12 months). These results suggest that ploidy changes are rare in this in vitro system, and do not significantly increase during long-term cultures. Microscopical studies of the microspore embryos in various stages revealed a healthy and well developed anatomy with no aberrant or chimeric structures. The general morphology of embryos appearing at different times after plating, looked similar to that of earlier embryos, as well as the zygotic embryos, indicating that they represent high quality material for cork oak breeding.
Keywords: Cytochemistry; DNA-Analysis; flow cytometry; haploid embryos; immunocyto- chemistry; Quercus suber L.

Microspore-derived embryos from Quercus suber anthers mimic zygotic embryos and maintain haploidy in long-term anther culture. - Bueno, María a; Gomez, Arancha; Sepulveda, Federico; Seguí, José M.; Testillano, Pilar S.; Manzanera, Jose a; Risueño, Maria-Carmen (Journal of plant physiology, 2003)
Microspore-derived embryos produced from cork oak anther cultures after long-term incubations (up to 10-12 months) were analysed in order to determine the genetic variability and ploidy level stability, as well as morphology, developmental pattern and cellular organisation. Most of the embryos from long-term anther cultures were haploid (90.7%), corresponding to their microspore origin. The presence of a low percentage of diploid embryos (7.4%) was observed. Microsatellite analysis of haploid embryos, indicated different microspores origins of the same anther. In the diploid embryos, homozygosity for different alleles was detected from anther wall tissues, excluding the possibility of clonal origin. The maintenance of a high proportion of haploid embryos, in long-term anther cultures, is similar in percentage to that reported in embryos originating after 20 days of plating (Bueno et al. 1997). This suggests that no significant alterations in the ploidy level occurred during long incubations (up to 12 months). These results suggest that ploidy changes are rare in this in vitro system, and do not significantly increase during long-term cultures. Microscopical studies of the microspore embryos in various stages revealed a healthy and well developed anatomy with no aberrant or chimeric structures. The general morphology of embryos appearing at different times after plating, looked similar to that of earlier embryos, as well as the zygotic embryos, indicating that they represent high quality material for cork oak breeding.
The following values have no corresponding Zotero field: accession-num: 12964871
Keywords: Cytochemistry; DNA-Analysis; flow cytometry; haploid embryos; immunocyto- chemistry; Quercus suber L.